Konseling Cinematherapy tentang Kecemasan Sosial di SMK Negeri 2 Semarang - Rubi Rimonda; Onetusfifsi Putra; Eva Flourentina Kusumawardani; Meutia Paradhiba; Perry Boy Chandra Siahaan; Mardi Fadillah; Firman Firdauz Saputra (Idea Pengabdian Masyarakat, 2022)
Social anxiety is a problem that many students encounter; this can have an impact on hampering optimal academic or social development for them at school. Students with social anxiety will have problems forming or maintaining friendships, avoid going into group situations, and be socially isolated or bullied, and this causes them to avoid certain schools or classes. Although not all individuals who experience social anxiety consistently avoid social evaluative situations, most report an inability to interact in social gatherings. Social anxiety problems will interfere with individual activities and lives if not addressed immediately, so counseling is essential. This service is carried out at SMK Negeri 2 Semarang City. The devotion method uses cinematherapy techniques. The service results show the counselee's enthusiasm to participate in the counseling session from beginning to end. Counselees learn to dare to ask questions, discuss in groups, and try to apply the examples they get in the cinematherapy technique.